MRI of posterior eye shape and its associations with myopia and ethnicity. Issue 9 (2nd December 2019) - Lim, Laurence Shen; Matsumura, Saiko; Htoon, Hla Myint; Tian, James; Lim, Shin Bin; Sensaki, Sonoko; Chen, Christopher; Hilal, Saima; Wong, Tien Yin; Cheng, Ching Yu; Kuo, Anthony; Saw, Seang Mei
Abstract : Purpose: To evaluate posterior eye shape variations across a wide refractive error range using brain MRI in a multiethnic cohort. Methods: Adult subjects in the multiethnic Singapore Epidemiology of Eye Disease study were included. Spherical equivalent (SE) was measured using subjective refraction, and axial length (AL) was measured using optical biometry. MRI was performed using a 3-Tesla whole body scanner with a 32-channel head coil. The radii and asphericity based on fitting of the posterior two-thirds of the eye (240°) were calculated. The refractive error status was categorised as myopic (SE<−0.5 D) or non-myopic (SE≥−0.5 D). Results: A total of 450 adult participants (mean age 64.2±6.5 years old) were included. Less oblate asphericity was associated with more myopic SE, longer AL and with a refractive error categorisation of myopia (p<0.001 for all). Asphericity values were less oblate in myopic compared with non-myopic eyes (p<0.001). Multivariate analysis showed that Chinese subjects had less oblate eyes than Malay and Indian subjects, especially in non-myopic eyes. Conclusions: A less oblate posterior eye shape was associated with myopic eyes. Chinese eyes have less oblate shapes than Malay and Indian eyes, especially in non-myopic eyes.